Differentiation and coordination within a composite training policy providing efficient support namely to isolated museum professionals (Cadernos de Sociomuseologia, 2012)
In Portugal, namely in municipal museums, the reduced percentage of museum professionals that have a stable administrative position imposes a high degree of polyvalence allowing them to coordinate, often by themselves, the quotidian activities at the museum(s) they run.